2021
DOI: 10.1007/s10668-021-01329-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pro-environmental behaviour and its determinants during long-term period in a transition country as Lithuania

Abstract: The changes in pro-environmental behaviour, whether people become more environmentally friendly or not, have been analysed very scarcely. Therefore, the aim of this paper was to analyse the changes in pro-environmental behaviour and its determinants in Lithuania as a transition European Union country comparing years 2011 and 2020. Applying Chi-Square and t test statistics, the results showed a significant increase in performance of pro-environmental behaviour in 2020. Waste sorting and purchase of environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 77 publications
1
10
0
2
Order By: Relevance
“…European Commission, 2019; United Nations, 2019) underscore the importance of sustainable development in overcoming the challenges set by issues such as climate change. Education is thought to be key in preparing future generations for facing this issue (Amézaga et al, 2021;Minelgaitė & Liobikienė, 2021;Sekhar & Raina, 2021). However, before educational efforts can be monitored, research should ask whether formal education in schools and classrooms affects students' action competence regarding sustainable development (ACiSD).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…European Commission, 2019; United Nations, 2019) underscore the importance of sustainable development in overcoming the challenges set by issues such as climate change. Education is thought to be key in preparing future generations for facing this issue (Amézaga et al, 2021;Minelgaitė & Liobikienė, 2021;Sekhar & Raina, 2021). However, before educational efforts can be monitored, research should ask whether formal education in schools and classrooms affects students' action competence regarding sustainable development (ACiSD).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These policy recommendations build onto the 17 Sustainable Development Goals (United Nations, 2015), which aim at working towards sustainable development, which was defined as a process of mutually interacting environmental, social, and socio-economic perspectives. Educational efforts at all levels are paramount if we are to promote environmental and sustainable behaviour that would allow to take on the challenges involved (Amézaga et al, 2021;Minelgaitė & Liobikienė, 2021;Sekhar & Raina, 2021). In order to monitor these efforts, measurement of learning outcomes is crucial (Amézaga et al, 2021;UNESCO, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Se destaca que los cambios en el comportamiento proambiental, tanto si las personas se vuelven más respetuosas con el medio ambiente como si no, han sido escasamente analizados (Minelgaitė y Liobikienė, 2021). Los crecientes problemas ambientales son ahora una preocupación mundial, en parte debido al comportamiento humano que generalmente no es respetuoso con el medio ambiente, como botar basura, usar vehículos en exceso, derrochar el consumo de recursos, quemar combustibles fósiles, consumir productos no reciclables y productos no orgánicos.…”
Section: Figuraunclassified
“…Values are the basic priorities, interests, beliefs, and attitudes of a society, a group, or an individual that define the principles by which a person should behave [15]. Values influence attitudes toward the environment, perceptions of the consequences of behavior, and acceptance of responsibility, and contribute to environmentally friendly behavior [16]. Jančius [17] observed that values encompass human behavior for the sake of well-being by encouraging reflection on and cultivation of other values and behaviors, and become more effective in building the well-being of oneself and others.…”
Section: The Concept and Meaning Of Valuesmentioning
confidence: 99%